Kualitas Hidup Anak dengan Tinea Kapitis - Ericko Gilrandy Sanjaya; Putu Dyah Ayu Saraswati; Nena Mawar Sari (Cermin Dunia Kedokteran, 2023)
Tinea capitis is not life threatening, but can affect patient’s psychological state. It was reported that a case of tinea capitis in a girl which caused psychological disorders as evidenced by the CDQLI (children dermatology quality life index) and DMHC (Denpasar Medical Health Centre) assessment methods. Oral and topical therapy with griseovulfin provides clinical and psychological improvement.